The Effect of Virtual Reality Technology on the Imagery Skills and Performance of Target-Based Sports Athletes - Bedir, Deniz; Erhan, Süleyman Erim (Frontiers in Psychology, 2021)
The aim of this study is the examination of the effect of Virtual Reality Based Imagery training programs on the shot performance and visualization skills of athletes and, and to conduct a comparison with Visual Motor Behavior Rehearsal and Video Modeling. In the research, mixed research method and sequential explanatory design were used. In the quantitative dimension of the study the semi-experimental model was used, and in the qualitative dimension the case study design was adopted. The research participants were selected from athletes who were involved in our target sports: curling (n = 14), bowling (n = 13) and archery (n = 7). All participants were randomly assigned to Visual Motor Behavior Rehearsal and Video Modeling (n = 11), Virtual Reality Based Imagery (n = 12) and Control (n = 11) groups through the "Research Randomizer" program. The quantitative data of the study was: The weekly shot performance scores of the athletes and the data obtained from the “Movement Imagery Questionnaire-Revised”. The qualitative data was obtained from the data collected from the semi-structured interview guide, which was developed by researchers and field experts. According to the results obtained from the study, there were statistically significant differences between the groups in terms of shot performance and imagery skills. Virtual Reality Based Imagery training athletes showed more improvement in the 4-week period than the athletes in the Visual Motor Behavior Rehearsal and Video Modeling group, in terms of both shot performance and imagery skills. In addition, the Virtual Reality Based Imagery group adapted to the imagery training earlier than the Visual Motor Behavior Rehearsal and Video Modeling group. As a result, it was seen that they showed faster development in shot performances. From these findings, it can be said that Virtual Reality Based Imagery program is more efficient in terms of shooting performance and imagery skills than Visual Motor Behavior Rehearsal and Video Modeling, which is the most used imaging training model.